The Future of Robotics: A Review of AI-Enabled Robotics Research, Development, and Applications - Harmandeep Kaur; Jaspreet Kaur (International Journal of Robotics and Automation in Mechanics, 2025)
Robotics powered by artificial intelligence (AI) is transforming contemporary industries by empowering machines to learn, adapt, and operate on their own in intricate, changing contexts. The breadth and capabilities of automation have been greatly expanded by the convergence of AI technologies with robots, including machine learning, deep learning, computer vision, and natural language processing (NLP). With an emphasis on technological advancements, application areas, and research advances, this study examines current trends in AI-enabled robotics. AI enables robots to carry out activities that were previously thought to be too risky or complex for conventional automation systems. These include industrial assembly, robotic surgery, autonomous navigation, real-time object detection, and customized service provision. Robotic decision-making and environmental interaction are being improved by key enablers such as sensor technology, sensor fusion, 3D perception, and sophisticated control algorithms. The application of intelligent robotic systems is revolutionizing user experience and productivity, from AI-driven healthcare assistants to collaborative robots (cobots) in manufacturing. The study also explores state-of-the-art developments such as quantum AI for real-time, high-efficiency processing, neuromorphic computing for human-like cognition, and reinforcement learning for dynamic task optimization. The research also looks at issues including high computational needs, moral conundrums, unclear regulations, cybersecurity threats, and societal repercussions like employment displacement that prevent the widespread application of AI in robots. New developments like autonomous decision-making and multimodal human-robot interaction bring up significant issues with trust, responsibility, and privacy. In addition to offering a thorough analysis of the state of artificial intelligence (AI) in robotics today, this study identifies exciting avenues for future research, including the establishment of standardized ethical frameworks, integration with quantum computing, and the quest for artificial general intelligence (AGI). In the end, the ethical and creative development of AI-powered robots has promise for changing industries, enhancing human well-being, and advancing sustainable technology.
Keywords: Computer vision; Machine Learning; Robotics; artificial intelligence; autonomous systems; natural language processing